Satisfaction with life as a predictor of quality of life at work and work performance in health workers - Macedo Alvarez, Jennifer (2023)
Objective: to identify whether life satisfaction predicts quality of life at work and work performance in health workers. Methodology: non-experimental, cross-sectional design of correlational analysis and structural equation modeling in 308 health workers. Psychologists, physicians, neurologists, nurses, nutritionists, obstetricians, dentists, nursing, pharmacy and laboratory technicians of both sexes participated, belonging to 3 health centers in the San Martín Region, Peru, who were selected through non-invasive sampling. probabilistic. Data collection was carried out through the quality of life scale, the satisfaction with life scale and the job performance scale. Results: there is a relationship between satisfaction with life, quality of life at work and job performance (p<.05). Conclusion: the quality of life at work has no effect on work performance in health workers